The tradition of Kenduri Motor, the community of the Teluk Ondan Village, Bantan District, Bengkalis Regency, Riau Province Indonesia / Reno Firdaus and Zulfikar Hasan - Firdaus, Reno; Hasan, Zulfikar (Faculty of Communication & Media Studies, 2023)
The tradition of motorized feasts carried out by the people of Teluk Ondan is a hereditary tradition carried out by fishermen when their motorbikes will be used to catch fish. But nowadays the tradition of motorized kenduri is rarely carried out by fishermen so some people do not know the readings and values contained in the tradition of motor festivities. The purpose of this research on motorized kenduri is to find out the readings used and what values are contained in the tradition of motorized kenduri of the Dusun Teluk Ondan community. The method used in this study is a qualitative descriptive method with purposive sampling data collection techniques where only local traditional leaders are the resource persons. The results showed that the readings used for motorized feasts were Surat Al-Fatihah, Surah Al-Ikhlas (3 times), Surah Al-Falaq, Surah An-Nas, Surah Al-Fatihah, Surah Al-Baqarah verses 1-5, Surah Al -Baqarah verse 163, Verse of the chair, Surah Al-Baqarah verse 284-286, Surah Hud verse 73, Surah Al-Ahzab verse 33, Surah Al-Ahzab verse 56, Shalawat to the prophet (3 times), Surah Ali Imran verse 173 and Surah Al-Anfal verse 40, Hauqalah, Istighfar (3 times), Tahlil 160 times, Shahada, and prayer tahlil, while the values contained in motor feasts are: religious, social, cultural, educational, and life values.